Hybrid EMT Phenotype and Cell Membrane Tension Promote Colorectal Cancer Resistance to Ferroptosis - Xiaowei Wei; Yutong Ge; Yaolin Zheng; Sunyan Zhao; Yuhan Zhou; Yuhan Chang; Nuofan Wang; Xiumei Wang; Juan Zhang; Xuanchang Zhang; Liqiao Hu; Youhua Tan; et al. (Advanced Science)
Abstract Intratumoral heterogeneity, including epithelial–mesenchymal transition (EMT), is one major cause of therapeutic resistance. The induction of ferroptosis, an iron‐dependent death, has the potential in overcoming this resistance to traditional treatment modalities. However, the roles of distinct EMT phenotypes in ferroptosis remain an enigma. This study reports that 3D soft fibrin microenvironment confers colorectal cancer (CRC) cells hybrid EMT phenotype and high level of resistance to ferroptosis. The activation of histone acetylation and WNT/β‐catenin signaling drives this EMT phenotypic transition, which promotes the defense of 3D CRCs against ferroptosis via glutathione peroxidases/ferritin signaling axis. Unexpectedly, E‐cadherin knockout in 3D but not 2D CRCs mediates an integrin β3 marked‐late hybrid EMT state and further enhances the resistance to ferroptosis via integrin‐mediated tension and mitochondrial reprogramming. The inhibition of integrin αvβ3‐mediated tension and WNT/β‐catenin‐mediated hybrid EMT sensitizes 3D CRCs with and without E‐cadherin deficiency to ferroptosis in vivo, respectively. Further, the EMT phenotype of patient‐derived tumoroids is associated with CRC therapeutic resistance. In summary, this study uncovers previously unappreciated roles of hybrid EMT and cell membrane tension in ferroptosis, which not only predict the treatment efficacy but also potentiate the development of new ferroptosis‐based targeted therapeutic strategies.